The return of Lucretius to Renaissance Florence - Brown, Alison (I Tatti studies in Italian Renaissance history, 2010)
The early Epicurean revival in Florence and Italy -- Medicean Florence : Ficino and Bartolomeo Scala -- Republican Florence : the university lectures of Marcello Adriani -- Niccol Machiavelli and the influence of Lucretius -- Lucretian networks in the late fifteenth and early sixteenth centuries -- Appendix : notes on Machiavelli's transcription of MS Vat. Rossi 884